Endoscopic treatment of esophageal fistulas after esophagectomy with injection of an alpha-cyanoacrylate monomer: a phase II study - Ojima, Toshiyasu; Nakamura, Masaki; Nakamori, Mikihito; Katsuda, Masahiro; Hayata, Keiji; Tsuji, Toshiaki; Maruoka, Shimpei; Yamaue, Hiroki (Endoscopy International Open, 2018)
Background and study aims Interventional endoscopic treatments including the application of glue are becoming more frequently used for the treatment of esophageal fistulas. However, there are no prospective studies of endoscopic treatment for esophageal fistulas. This prospective study aims to investigate the efficacy and safety of endoscopic injection of alpha-cyanoacrylate monomer for intractable esophageal fistulas. Patients and methods This single-center prospective phase II trial included patients with more than 1 wk of conservative medical treatment for intractable esophageal fistulas after esophagectomy. In the image-guided therapy suite, a mixture of alpha-cyanoacrylate monomer and oily contrast agent in a ratio of 0.3 to 1.7 mL was endoscopically injected through the fistula.Results Twenty-five patients who underwent esophagectomy at Wakayama Medical University Hospital were enrolled in this study. The primary disease was esophageal cancer in 16 patients (64 %) and gastric cancer in the remaining 9 patients (36 %). Complete closure of the esophageal fistula was performed in 22 patients after endoscopic injection of alpha-cyanoacrylate monomer. The overall success rate was 88 %. There was no fistula recurrence in any successful closure cases. Three patients with failed esophageal fistula closure had esophageal cancer with cervical esophageal fistulas and required reoperation of the fistulectomy under general anesthesia. No complications associated with this endoscopic treatment were detected. Conclusions Endoscopic treatment with injection of alpha-cyanoacrylate monomer facilitated healing of post-esophagectomy fistula in 88 % of patients without complications. This suggests that the treatment is effective and safe for patients with esophageal fistulas.